2002
DOI: 10.1097/01.asn.0000013298.11876.bf
|View full text |Cite
|
Sign up to set email alerts
|

Withdrawal of Cyclosporine or Prednisone Six Months after Kidney Transplantation in Patients on Triple Drug Therapy

Abstract: ABSTRACT. Uncertainty exists regarding the necessity of continuing triple therapy consisting of mycophenolate mofetil (MMF), cyclosporine (CsA), and prednisone (Pred) after kidney transplantation (RTx). At 6 mo after RTx, 212 patients were randomized to stop CsA (n = 63), stop Pred (n = 76), or continue triple drug therapy (n = 73). The MMF dose was 1000 mg twice daily, target CsA trough levels were 150 ng/ml, and Pred dose was 0.10 mg/kg per d. Follow-up was until 24 mo after RTx. Biopsy-proven acute rejectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
91
1
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(101 citation statements)
references
References 30 publications
8
91
1
1
Order By: Relevance
“…Thus, considering the incidence of AR previously reported in different randomized trials (11)(12)(13) and in our study, the new immunosuppressive drug MMF did not lead to a completely safe CsA discontinuation. Otherwise, the two pivotal trials of CsA elimination conducted with sirolimus showed different results.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Thus, considering the incidence of AR previously reported in different randomized trials (11)(12)(13) and in our study, the new immunosuppressive drug MMF did not lead to a completely safe CsA discontinuation. Otherwise, the two pivotal trials of CsA elimination conducted with sirolimus showed different results.…”
Section: Discussionsupporting
confidence: 68%
“…In stable renal transplant recipients, CsA withdrawal under MMF was also found to be a safe procedure on the basis of the risk of AR and renal function (8,9), although histologic deterioration was observed in 50% of patients (10). Finally, the incidence of AR after CsA discontinuation under MMF was evaluated in three randomized trials (11)(12)(13). The risk for AR was found to be significantly increased in two of these studies (11,12), and a trend to a higher incidence was shown in the third one (13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 We did not observe any increase in acute rejection rates after sirolimus conversion as mentioned in earlier studies. 18 The frequency of acute rejection is not increased in our study. It may be because conversion was made at 30th month.…”
Section: Discussioncontrasting
confidence: 44%
“…The first was reported by Smak Gregoor et al (40) and was designed as a prospective randomized study in primary transplant recipients treated with an immunosuppression regimen consisting of cyclosporine, MMF, and prednisone. The objective of this study was to assess the safety of withdrawal of cyclosporine (50% reduction for 2 wk before discontinuation) or prednisone at 6 mo after transplantation compared with the continuation of triple therapy (Figure 2).…”
Section: Trials With Cni-sparing Regimensmentioning
confidence: 99%